2019
DOI: 10.1186/s40478-019-0802-7
|View full text |Cite
|
Sign up to set email alerts
|

The p75NTR neurotrophin receptor is required to organize the mature neuromuscular synapse by regulating synaptic vesicle availability

Abstract: The coordinated movement of organisms relies on efficient nerve-muscle communication at the neuromuscular junction. After peripheral nerve injury or neurodegeneration, motor neurons and Schwann cells increase the expression of the p75NTR pan-neurotrophin receptor. Even though p75NTR targeting has emerged as a promising therapeutic strategy to delay peripheral neuronal damage progression, the effects of long-term p75NTR inhibition at the mature neuromuscular junction have not been elucidated. We performed quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 99 publications
2
15
0
Order By: Relevance
“…The Kondziela's inverted grid test measures an animal's strength and coordination. Additionally, we used a weight test to measure the strength of the animals and confirmed the previous observation that p75NTR ExonIII KO animals are weaker than WT animals (Reddypalli et al, 2005;Pérez et al, 2019). We could not detect differences between males and females p75NTR ExonIII KO.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The Kondziela's inverted grid test measures an animal's strength and coordination. Additionally, we used a weight test to measure the strength of the animals and confirmed the previous observation that p75NTR ExonIII KO animals are weaker than WT animals (Reddypalli et al, 2005;Pérez et al, 2019). We could not detect differences between males and females p75NTR ExonIII KO.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, deletion of p75NTR only in the granule cell layer or the cerebellum recapitulates the gait defect ( Zanin et al, 2016 ). Recent findings suggest that p75NTR is also critical for forming the neuromuscular junction and normal strength ( Reddypalli et al, 2005 ; Dokter et al, 2015 ; Pérez et al, 2019 ). In summary, many research groups have shown that p75NTR KO animals have dysfunctions in gait, strength, balance, and various neuronal processes.…”
Section: Introductionmentioning
confidence: 99%
“…Involved in pro-apoptotic signaling during development, but downregulated in the mature nervous system, the p75 NTR receptor is also re-expressed in neurons after disease or trauma (Dechant and Barde, 2002 ), possibly impacting LV efficacy. For example, p75 NTR expression is increased in SOD1 G93A mice motor neurons and human ALS tissue (Lowry et al, 2001 ), and plays a key role in organizing and maintaining NMJ connectivity (Pérez et al, 2019 ). Moreover, NCAM expression is a major regulator of synaptic remodeling in pre-synaptic NMJ terminals (Chipman et al, 2014 ) and levels are dysregulated in ALS (Jensen et al, 2016 ), which could also affect LV binding.…”
Section: Influence Of Pathologymentioning
confidence: 99%
“…Strikingly, FMNs are more susceptible to ALS pathology, whereas SMNs are predominantly resistant (Nijssen et al, 2017). This FMN preferential vulnerability has been observed in SOD1 (Frey et al, 2000;Pun et al, 2006;Tremblay et al, 2017;Allodi et al, 2021), TDP-43 (Ebstein et al, 2019), FUS (Sharma et al, 2016) and C9ORF72 (Liu et al, 2016) mutant mice, with limb-onset ALS accounting for ~70% of human pathology (Kiernan et al, 2011), suggestive of preferential FMN vulnerability conserved across species.…”
Section: Introductionmentioning
confidence: 82%
“…Activation of these pathways is dampened by a truncated TrkB receptor isoform (TrkB.T1) lacking the kinase domain, which sequesters synaptic BDNF (Haapasalo et al, 2002). The physiological roles of p75 NTR are equally complex, with high affinity for pro-neurotrophins that control neuronal apoptosis during development, whilst modulating neurotransmitter availability and NMJ organisation in the mature nervous system (Pérez et al, 2019). BDNF binding triggers TrkB.FL, TrkB.T1 and p75 NTR homoand/or hetero-dimerisation (Skeldal et al, 2011), and each complex elicits distinct signalling outputs (e.g., TrkB.FL-TrkB.T1 heterodimers inhibit TrkB.FL autophosphorylation (Hurtado et al, 2017)).…”
Section: Introductionmentioning
confidence: 99%